Measuring Surgical Outcomes in Subaxial Degenerative Cervical Spine Disease Patients: Minimum Clinically Important Difference as a Tool for Determining Meaningful Clinical Improvement. Issue 2 (11th November 2013) - Auffinger, Brenda; Lam, Sandi; Shen, Jingjing; Roitberg, Ben Z.
Abstract: BACKGROUND: Although the concept of minimum clinically important difference (MCID) as a measurement of surgical outcome has been extensively studied, there is lack of consensus on the most valid or clinically relevant MCID calculation approach. OBJECTIVE: To compare the range of MCID threshold values obtained by different anchor-based and distribution-based approaches to determine the best clinically meaningful and statistically significant MCID for our studied group. METHODS: Eighty-eight consecutive patients undergoing surgery for subaxial degenerative cervical spine disease were analyzed from a prospective blinded database. Preoperative, 3-, and 6-month postoperative patient reported outcome (PRO) scores and blinded surgeon ratings were collected. Four calculation methods were used to calculate MCID threshold values: average change, change difference, minimum detectable change, and receiver operating characteristic (ROC) curve. Three anchors were used to evaluate meaningful improvement postsurgery: health transition item, patient overall status, and surgeon ratings. RESULTS: On average, all patients had a statistically significant improvement ( P < .001) postoperatively for neck disability index (score 27.42 preoperatively to 19.42 postoperatively), physical component of the Short Form of the Medical Outcomes Study (SF-36) (33.02–42.23), mental component of the SF-36 (44–50.74), and visual analog scale (2.85–1.93). The 4 MCID approaches yielded a range of values for each PRO: 2.23 to 16.59 for physical component of the SF-36, 0.11 to 16.27 for mental component of the SF-36, and 2.72 to 12.08 for neck disability index. In comparison with health transition item and patient overall status anchors, the area under the ROC curve was consistently greater for surgeon ratings for all 4 PROs. CONCLUSION: Minimum detectable change together with surgeon ratings anchor appears to be the most appropriate MCID method. Based on our findings, this combination offers the greatest area under the ROC curve (threshold above the 95% confidence interval). The choice of the anchor did not significantly affect this result.